2020
DOI: 10.7759/cureus.10247
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics in Inflammatory Bowel Disease: Are We Back to Square One?

Abstract: Inflammatory bowel disease (IBD) is a chronic inflammatory condition of the alimentary tract whose incidence has been increasing over the past few years. Even though there is a complex interplay of several factors in the pathogenesis of IBD, a decrease in the diversity of intestinal microbiome is commonly found in patients. Extensive research is directed towards the alteration of this microbiome to improve the symptoms of IBD. Probiotics, prebiotics, antibiotics, and diet are studied in this regard extensively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…They analyzed three RCTs—two of them showed a significant improvement in patients’ QoL, and one study found no difference. The researchers concluded that the results of their analysis may indicate that probiotics improve the QoL of patients with IBD [ 68 ].…”
Section: Probioticsmentioning
confidence: 99%
“…They analyzed three RCTs—two of them showed a significant improvement in patients’ QoL, and one study found no difference. The researchers concluded that the results of their analysis may indicate that probiotics improve the QoL of patients with IBD [ 68 ].…”
Section: Probioticsmentioning
confidence: 99%
“…10 Probiotics usually promote health by regulating the endostasis of intestinal microorganisms, and Lactobacillus , Bifidobacterium and various probiotic complexes are widely used in UC alleviation studies. 11 In addition, the metabolites and components of probiotics, also known as postbiotics, are functional bioactive compounds produced during microbial fermentation, such as proteins, extracellular polysaccharides, bacteriocins and short-chain fatty acids (SCFAs). 12 SCFAs (mainly acetic acid, propionic acid and butyric acid) can be sensed by G protein-coupled receptors and thus participate in downstream immune responses in the gut.…”
Section: Introductionmentioning
confidence: 99%
“…Among IBD patients, probiotics have gained a great interest due to their feature to alleviate clinical symptoms and to improve the quality of life, either during periods of exacerbation or remission (13)(14)(15). In animal model, different strains of lactic acid bacteria, e.g., Bifidobacterium longum (16), Lactococcus lactis (17), Lactobacillus plantarum (recently reclassified as Lactiplantibacillus plantarum) (18), Lactobacillus reuteri (recently renamed Limosilactobacillus reuteri) (19) have been reported to modulate the gut microbiota composition leading to a restored intestinal barrier function.…”
Section: Introductionmentioning
confidence: 99%